Hanan al-cinema : affections for the moving image - Marks, Laura U., 1963- (The MIT Press, 2015)
An examination of experimental cinema and media art from the Arabic-speaking world that explores filmmakers' creative and philosophical inventiveness in trying times.
Keywords: Motion pictures -- Arab countries -- History -- 21st century.; Documentary films -- Arab countries -- History -- 21st century.; Motion picture industry -- Arab countries -- History -- 21st century.; Video art -- Arab countries -- 21st century.; Cinéma -- États arabes -- Histoire -- 21e siècle.; Cinéma -- Industrie -- États arabes -- Histoire -- 21e siècle.; Art vidéo -- États arabes -- 21e siècle.; PERFORMING ARTS -- Reference.; Documentary films; Motion picture industry; Motion pictures; Video art; Arab countries; Arabländerna.; Dokumentärfilm.; Filmindustrin, Arabländerna.; 2000-2099; ARTS/Photography & Film/History, Theory & Criticism; DIGITAL HUMANITIES & NEW MEDIA/New Media Art; CULTURAL STUDIES/Global Studies; History